How physicians discuss uncertainty with parents in neonatal and pediatric intensive care units.: Presenter(s): Sanne Prins, Amsterdam University Medical Center, Netherlands. (April 2023) - Linn, Annemiek; van Kaam, Anton; van de Loo, Moniek; van Woensel, Job; van Heerde, Marc; Dijk, Peter; Kneijber, Martin; de Hoog, Matthijs; Simons, Sinno; Dijkstra, Sandra; Olthuis, Annelies; Akkermans, Aranka; et al.
Abstract : Background: In neonatal and pediatric intensive care, physicians make treatment decisions on the child's behalf in close cooperation with parents. Prevailing uncertainties make these decisions extra complex. Adequately communicating with parents may be pivotal, as this could improve the decision-making process and parents' coping in the short and longer term. In this observational study, we aimed to investigate how physicians discuss uncertainty with parents, and how this discussion develops over time during the child's illness- and treatment trajectory. Methods: Physicians working at neonatal and pediatric intensive care units of three university medical centers audio recorded their conversations with parents, starting from the moment doubts arose whether treatment was still in the child's best interests. The researchers inductively coded transcripts of these conversations (Nconversations= 29; Ncases= 8). The identification of the topic to which uncertainty pertained and which communicative strategy the physician used, guided the analysis. Analysis was done by means of MAXQDA. Results: Physicians discussed many uncertainties with parents regarding a large variety of topics, including uncertainty about the efficacy, risks and necessity of treatment, and the process of dying. Physicians adapted the way they discussed uncertainty to the specific phase of the child's illness and treatment trajectory. When there were still treatment options available, physicians primarily provided explanations or presented short-term action plans. When the child's death was imminent, physicians rather eliminated most uncertainty. Conclusions: By means of this prospective study, we obtained a detailed overview of how physicians discuss uncertainty with parents. We identified a wide array of strategies available for physicians to discuss uncertainty throughout different phases of the child's illness- and treatment trajectory. Our insights will help physicians to be more aware of the communicative strategies they use and to better tailor these strategies to parents' specific needs in and over the phases of the trajectory.